2009
DOI: 10.1021/jp904276t
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Improved Electrochemical Performances of Fe-Substituted 5 V Spinel Cathode LiMn1.5Ni0.5O4

Abstract: Partial substitution of Fe for Ni alone or both for Ni and Mn in the 5 V spinel cathode LiMn1.5Ni0.5O4 has been investigated by characterizing the samples by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), charge−discharge measurements in lithium cells, electrochemical impedance spectroscopy (EIS), chronoamperometry (CA), and X-ray photoelectron spectroscopy (XPS). The Fe-substituted samples exhibit remarkably superior cycling performances and higher rate capabilities than the pristin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
200
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 294 publications
(217 citation statements)
references
References 36 publications
6
200
2
1
Order By: Relevance
“…Li1.2Mn0.56Ni0.16Co0.08−xAlxO2 (x=0.05) shows the highest rate capacity and excellent cycling stability cycled at high charge-discharge rate, but the pristine one exhibits poor rate-capability. It has been reported that the lithium ion insertion/extraction kinetics corresponding to the lithium-ion diffusion in the bulk of the material affect the rate capability [48]. As mentioned above, the lithium-ion diffusion ability is the control step at high charge-discharge current density, and the charge-discharge current density significantly affects the discharge capacity.…”
Section: Resultsmentioning
confidence: 99%
“…Li1.2Mn0.56Ni0.16Co0.08−xAlxO2 (x=0.05) shows the highest rate capacity and excellent cycling stability cycled at high charge-discharge rate, but the pristine one exhibits poor rate-capability. It has been reported that the lithium ion insertion/extraction kinetics corresponding to the lithium-ion diffusion in the bulk of the material affect the rate capability [48]. As mentioned above, the lithium-ion diffusion ability is the control step at high charge-discharge current density, and the charge-discharge current density significantly affects the discharge capacity.…”
Section: Resultsmentioning
confidence: 99%
“…into the solid structure, thus restricting the Mn 3+ species under feasible operating voltages. As a prominent example, the Mn-rich LiMn2-xNixO4 electrodes [292][293][294][295][296][297][298][299], which consist primarily of Mn 4+ , should not succumb to such undesirable interactions with electrolytes. Substitution of Mn with Ni, as opposed to other transition metals, has been met favourably due to good cycling stability, access to the Ni 4+/3+ redox couple below 4.9 V and the appearance of only one distinct plateau in the voltage profile (~4.7 V), compared to a bi-plateauing afforded by other transition metals [299].…”
Section: Mixed Spinel and Layered Oxidesmentioning
confidence: 99%
“…A few drawbacks of LiMn1.5Ni0.5O4 electrodes, however, mar their application: The formation of an impurity phase LixNi1-xO seemingly worsens electrochemical performance over time and while accessible, the Ni 4+/3+ redox couple falls at potentials where electrolyte decomposition is prevalent. Addition of other transition metal cations into LiMn2-xNixO4 systems has been adopted and could prevent the formation of LixNi1-xO phases, together with reducing the cycling-induced lattice expansion [292,[300][301][302][303][304]. As an example, partial substitution of Fe for Mn or Ni in LiMn1.5Ni0.5O4 electrodes has led to enhanced electrochemical activity, most notably in terms of cycling stability and rate performance [292] (Fig.…”
Section: Mixed Spinel and Layered Oxidesmentioning
confidence: 99%
“…Table 7 lists the second and 50th discharge capacities and capacity retentions. Because the chargedischarge process during the 1st cycle is often affected by extra reactions, such as a solid electrolyte interphase (SEI) formation, 18), 19) we evaluated the capacity retentions of the samples by the ratio of the capacities at the 50th cycle to the 2nd cycle. When chargedischarged over 2.754.30 V vs. Li/Li + for 50 cycles at room temperature, samples (B) and (C) showed a fast capacity fading.…”
Section: Electrode Propertymentioning
confidence: 99%